Global politics and education systems: towards education markets? - Leoncio Vega Gil (Springer, 2013)
Our paper has as its first aim to highlight the fact that the approach on which studies about educational policies or the politics of education (the second concept being more widely used in social sciences) have been based so far involves returning to the stance posited by J.A. Maravall -a category composed of ideas, foundations, mind-set, ideology, etc.; in other words, politics as an idea. A second analytical category would be expressed by norms, legislation, actions, practices, etc., which represent politics as regulation (Dutercq, 2005). Despite placing our study within the management of both categories from a methodological point of view, our focus is more specifically placed on the second interpretation. Thus, new education policies break the 'methodological nationalism' with a view to present standardized, mercantile and global discourses and practices as a demand of international education agencies. These global policies end, or begin, by building a social and practical network identified here as 'schooling market' and expressed through private ownership of schools and governance (the social use of education practices), which operates with different degrees of intensity across international education systems.